Factors Associated with the Choice of Female Sterilization as Contraception: A Scoping Review : - Juwi Amalia; Ni Komang Yuni Rahyani; Ni Nyoman Suindri (Viva Medika, 2026)
Female sterilization or tubectomy (Metode Operasi Wanita/MOW) is a highly effective permanent contraceptive method; however, its utilization remains relatively low, suggesting the influence of various non-medical factors on women’s decision-making. This study was conducted as a scoping review to identify and map factors associated with the selection of MOW among women of reproductive age. A systematic search of national and international databases was conducted based on predefined inclusion and exclusion criteria. Eleven eligible articles were analyzed through the stages of identification, screening, data charting, and synthesis. Seven key factors were identified: age, education, employment status, parity, knowledge, attitude, and husband’s support. Age ≥30 years and higher parity consistently emerged as dominant determinants. Adequate knowledge and positive attitudes toward permanent contraception significantly increased women’s willingness to choose MOW, while husband’s support was the strongest reinforcing factor. Overall, the selection of MOW is influenced not only by medical considerations but also by social, psychological, and cultural factors. Strengthening contraceptive education and promoting couple-centered counseling are essential to improve informed decision-making and increase acceptance of female sterilization.